Study the Effect of Adding Pharmaceutical Rennie Particles to Composite Materials with Polyester Matrix to be used in Medical Purposes - Marhoon, Ismail Ibrahim; Sallal, Hayder Abbas (Nahrain University College of Engineering Journal, 2014)
The study carried out on the Rennie filled unsaturated polyester composites of varying size and different filler concentration reveals changes of the mechanical and physical properties of the composites, these changes in the properties of the Rennie filled polymer composites make them suitable for their use in medical, biomedical and pharmaceutical applications on large extent. This work focuses on the preparation of base polymer matrix (unsaturated polyester) composite materials by (Hand Lay-Up) method, and studying the effect of selected grain size (25, 53, and 90) ?m of (Rennie) particles on some properties of the prepared composite. Some mechanical tests were used to evaluate the prepared system (Tensile, Compression, Impact, and Hardness) tests, and a physical test of (Water absorption %), and all tests were accomplished at room temperature. Maximum results of tensile strength, elongation at brake, young’s module, compression strength, flexural strength, flexural modulus, impact strength, hardness and water absorption were ((55.6MPa),( 2.36 %), (2550 MPa), (51.5 MPa), (77.33 MPa), (6072.8 MPa),( 4.48 KJ/m2), (87.5 Shore (D)) and (0.321%)) respectively at using (25?m) except for flexural modulus and water absorption at (90 ?m)..